Tiktok Sebagai Media Kreativitas di Masa Pandemi Covid-19 - Fanaqi, Chotijah (Jurnal Dakwah, 2021)
This study aims to see and interpret how Tik Tok is used as a medium to support creativity by its users during the pandemic of Covid-19. This research method is qualitative with an interpretive approach. This research was carried out during the pandemic of Covid-19, during November 2020, with data collection techniques through interview techniques, literature searches, and interpretation of data. Interviews were conducted with 14 TikTok application users using several methods, including face-to-face (with health protocols), Video Call, and WhatsApp Chat, on Tik Tok application users in the period November 2020. The results showed that the use of Tik Tok during the pandemic of Covid-19 is sufficient to support the creativity of its users. The indicators of creativity as stated by Guilford (2008) which include fluency in thinking, flexibility in thinking, and developing ideas are almost all felt by the participants as users of the Tik Tok account interviewed by the researcher. This is because users feel the use of the Tik Tok application is quite effective during the pandemic of Covid-19, where most of their daily activities are carried out at home, as an effort to avoid crowds and direct contact with other people as an effort to prevent the transmission of Covid-19. In addition to supporting creativity, the use of the Tik Tok application also has several other benefits including entertainment medium, interaction medium, promotional medium, medium of information sharing, and medium that can increase immunity. Keywords: Tik Tok, Medium of Creativity, Pandemic of Covid-19 Penelitian ini bertujuan untuk melihat dan menginterpretasikan bagaimana Tik Tok digunakan sebagai media penunjang kreativitas oleh para penggunanya di masa pandemi Covid-19.  Metode penelitian ini adalah kualitatif dengan pendekatan Interpretatif. Penelitian ini dilaksanakan pada masa pandemi Covid-19, yakni selama bulan November 2020, dengan teknik pengumpul data melalui teknik wawancara, penelusuran pustaka, serta interpretasi terhadap data. Wawancara dilakukan terhadap 14 pengguna aplikasi TikTok dengan menggunakan beberapa metode, diantaranya tatap muka (dengan protokol kesehatan), Video Call, dan Chat WhatsApp, pada pengguna aplikasi Tik Tok pada rentang waktu bulan November 2020. Hasil penelitian menunjukkan bahwa Penggunaan Tik Tok di masa pandemi Covid-19 cukup menunjang kreativitas para penggunanya. Indikator kreativitas sebagaimana dikemukakan oleh Gulford (2008) yang meliputi kelancaran berpikir, keluwesan berpikir, dan mengembangkan gagasan hampir semua dirasakan oleh para partisipan selaku pengguna akun Tik Tok yang diwawancarai oleh peneliti. Hal ini karenakan para pengguna merasakan pemanfaatan aplikasi Tik Tok cukup efektif di masa pandemi Covid-19 yang sebagian besar aktivitas sehari-hari banyak dilakukan di rumah, sebagai upaya menghindari kerumunan dan kontak langsung dengan orang lain sebagai upaya pencegahan penularan Covid-19. Selain menunjang kreativitas, penggunaan aplikasi Tik Tok juga   memiliki beberapa manfaat lain diantaranya seperti media hiburan, media interaksi, media promosi, media berbagi informasi, dan media yang bisa meningkatkan imun. Kata Kunci: Tik Tok, Media Kreativitas, Pandemi Covid-19